+0  
 
0
23
1
avatar

If \(\begin{align*} 4x-y+2z&=7,\\ 6x+3y+3z&=5, \end{align*}\) compute \(y.\)

 Jan 9, 2019
 #1
avatar+15350 
+2

Multiply FIRST equation by - 1.5 to get

-6x +1.5y -3z = -10.5      add it to second equation

6x +3y +3z =5

 

to get

 

4.5y = -5.5

y = -1.222      (  or  - 11/9)

 Jan 9, 2019
edited by ElectricPavlov  Jan 9, 2019

13 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.